Production and characterization of chitosan-based polymer particles with the precipitation collection method - Demırtaş, Hülya; Taşar, Şeyda; Kaya, Fatih; Özer, Ahmet (Fırat University, 2022)
In this study, a chitosan-based polymer particle was produced to be used as a sorbent. Gel particle production was carried out using chitosan samples with different acetylation degrees and molecular weights. The produced particles were characterized. In the first phase of the study, chitosan samples were provided and structural analyses were performed. In the second stage, polymer particle production was carried out by the precipitation-collection method. The morphological, structural, and physicochemical properties of the produced gel particles were examined. In the last step, the sorption efficiency of the particles (distilled water, oleic acid) was investigated. As a result, it was measured that the polymer particle diameters were to be between 3.388 and 3.903 mm and the densities of the particles were to be 0.389-0.416 g/cm3. Distilled water holding capacity of the particle which was produced with an 85 % DDA chitosan sample, was calculated as 0.523 g/gparticles, and the oleic acid holding capacity was determined as 0.286 g/gparticles. These values are approximately 20 % lower than the values obtained with the 75 % DDA chitosan sample. Low molecular mass chitosan sample sorbed 0.556 g distilled water per gram particle and 0.193 g oleic acid per gram particle. These values were calculated as 0.170 g/gparticle and 0.381 g/gparticle for the particles produced using high molecular weight chitosan samples, respectively. EDX analysis performed on the selected region, it was determined that the chitosan-based polymer particle consisted of 43.58 % C, and 49.83 % O.
Keywords: Chemical Engineering; Kimya Mühendisliği